2009
DOI: 10.1159/000216540
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Plasticity and Stress Inoculation-Induced Resilience

Abstract: Coping with mild early life stress tends to make subsequent coping efforts more effective and therefore more likely to be used as a means of arousal regulation and resilience. Here we show that this developmental learning-like process of stress inoculation increases ventromedial prefrontal cortical volumes in peripubertal monkeys. Larger volumes do not reflect increased cortical thickness but instead represent surface area expansion of ventromedial prefrontal cortex. Expansion of ventromedial prefrontal cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 118 publications
3
78
0
1
Order By: Relevance
“…Operationalizing early moderate stressors as involving temporary removal from the natal group, one study (Parker, Buckmaster, Justus, Schatzberg, & Lyons, 2005) found evidence of better performance in this condition than in the non-stressed condition on a later cognitive control task. Consistent with this finding, moderate stressors experimentally induced using this paradigm are associated with greater prefrontal myelination and larger ventromedial prefrontal cortices (Katz et al, 2009), areas of the brain that have been associated with poorer decision-making and reduced activation in suicidal individuals (Bridge et al, 2012; Currier & Mann, 2008; van Heeringen, Bijttebier, & Godfrin, 2011). …”
Section: Empirical Findingssupporting
confidence: 61%
“…Operationalizing early moderate stressors as involving temporary removal from the natal group, one study (Parker, Buckmaster, Justus, Schatzberg, & Lyons, 2005) found evidence of better performance in this condition than in the non-stressed condition on a later cognitive control task. Consistent with this finding, moderate stressors experimentally induced using this paradigm are associated with greater prefrontal myelination and larger ventromedial prefrontal cortices (Katz et al, 2009), areas of the brain that have been associated with poorer decision-making and reduced activation in suicidal individuals (Bridge et al, 2012; Currier & Mann, 2008; van Heeringen, Bijttebier, & Godfrin, 2011). …”
Section: Empirical Findingssupporting
confidence: 61%
“…Optogenetic stimulation of vmPFC neurons reverses depression-like behavior in mice susceptible to chronic social defeat stress [40]. Brief maternal separation in squirrel monkeys promotes stress inoculation and increases cortical volume in the vmPFC [41]. Also, neural activity in the vmPFC is both necessary and sufficient for the resistance to learned helplessness conferred by prior experience with controllable stress [18, 19, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Novelty seeking was also assessed in NS and SI squirrel monkeys at 2.5 years of age (Parker et al., 2007). Magnetic resonance imaging (MRI) of brain was conducted with NS and SI squirrel monkeys at 3.3 years of age (Katz et al., 2009) and place preference conditioning tests of NS and SI squirrel monkeys were conducted at 4.4 years of age (unpublished observations). Cognitive control, novelty seeking, place preference conditioning, and previous neuroimaging procedures were not conducted with SI + Mom squirrel monkeys and provided the opportunity to assess stress inoculation versus subsequent testing effects.…”
Section: Methodsmentioning
confidence: 99%